Nitrosomonas europaea MazF Specifically Recognises the UGG Motif and Promotes Selective RNA Degradation - Miyamoto, Tatsuki; Yokota, Akiko; Ota, Yuri; Tsuruga, Masako; Aoi, Rie; Tsuneda, Satoshi; Noda, Naohiro (Frontiers in Microbiology, 2018)
Toxin-antitoxin (TA) systems are implicated in prokaryotic stress adaptation. Previously, bioinformatics analysis predicted that such systems are abundant in some slowly growing chemolithotrophs; e.g., Nitrosomonas europaea. Nevertheless, the molecular functions of these stress-response modules remain largely unclear, limiting insight regarding their physiological roles. Herein, we show that one of the putative MazF family members, encoded at the ALW85_RS04820 locus, constitutes a functional toxin that engenders a TA pair with its cognate MazE antitoxin. The coordinate application of a specialised RNA-Seq and a fluorescence quenching technique clarified that a unique triplet, UGG, serves as the determinant for MazF cleavage. Notably, statistical analysis predicted that two transcripts, which are unique in the autotroph, comprise the prime targets of the MazF endoribonuclease: hydroxylamine oxidoreductase (hao), which is essential for ammonia oxidation, and a large subunit of ribulose 1,5-bisphosphate carboxylase/oxygenase (rbcL), which plays an important role in carbon assimilation. Given that N. europaea obtains energy and reductants via ammonia oxidation and the carbon for its growth from carbon dioxide, the chemolithotroph might use the MazF endoribonuclease to modulate its translation profile and subsequent biochemical reactions.